Analysis of Clinical Related Factors of Neonatal Hand-Foot-Mouth Disease Complicated With Encephalitis - Fang, Yanling; Lian, Chaowei; Huang, Dali; Xu, Liping (Frontiers in Neurology, 2020)
Object Analysis of risk factors related to short-term prognosis of neonatal HFMD complicated with encephalitis. Method The clinical data of 74 cases of neonatal HFMD complicated with encephalitis were analyzed retrospectively, and the risk factors related to short-term prognosis were found by univariate analysis and multivariate Logistic regression analysis.Result There were no significant differences in sex, age, duration of fever, treatment time, rash, reaction, crying, respiratory symptoms, digestive system symptoms, signs of high intracranial pressure, muscle tension, original reflection, CSF (cell number, chloride, lactate dehydrogenase) and aEEG among different groups (P > 0.05). However, there were significant differences in the state of consciousness, the level of protein in CSF, the level of inflammatory factors (CK-BB) and craniocerebral MRI(P＜0.05).